Antimitotic, antioxidant and genotoxic properties of Voacanga globosa (Bayag-USA) leaf extracts: An in vitro anticancer assessment - Chiu, Janelle Audre C. (Animo Repository, 2020)
Voacanga globosa (Blanco) Merr., a tree endemic to the Philippines, is used in Bataan as folk medicine to treat ulcers, wounds, and tumors. In this study, the antimitotic and genotoxic properties of V. globosa ethanol, ethyl acetate, and hexane crude extracts each of 1500 μg/mL, 1000 μg/mL, 500 μg/mL concentrations with distilled water as the negative control and acetaminophen 800 μg/mL as the positive control, were assessed on onion root meristematic cells using the root elongation assay and Allium cepa assay. Results show that V. globosa crude extracts exhibited antimitotic properties with the hexane extract showcasing the highest genotoxicity and antimitotic activity, having a percent mitotic index (%MI) of 1.04% and is comparable to that of acetaminophen. Cells showcasing aberrations and cell death including sticky metaphase, anaphasic bridges, irregular anaphase, and ghost cells were observed which indicates high cellular toxicity. Free radical scavenging assay was also done to determine the antioxidant activity of V. globosa ethanol and ethyl acetate extracts on 2,20- diphenyl-1-picrylhydrazyl (DPPH) radical. This yielded an IC50 value of 143.00 ±12.14 and 171.28 ±24.42 for ethanol and ethyl acetate respectively. The results highly imply that V. globosa is a promising source for chemotherapeutic drugs due to its high anticancer and antioxidant activity.